The Influence of Utilitarian and Hedonic Consumption Values on Consumer Attitude Towards Online Shopping and Purchasing Intentions - Redda, E.H. (Journal of Reviews on Global Economics, 2020)
Motivation: Online shopping is increasingly becoming a global phenomenon. In marketing literature, utilitarian and hedonic values are well-known consumption values that explain consumer behaviour and consumer decision-making. The purpose of this study is to determine the influence of utilitarian and hedonic consumption values on consumer attitude towards online shopping that, in turn, influences online purchasing intentions. In doing so, the study aims to deepen the understanding of consumer behaviour in an online environment, which marketing practitioners may find useful as the phenomenon of online shopping gains momentum in the 4th industrial revolution. Methodology and Methods: This study followed a descriptive research design, and a quantitative research method. Data (sample, n = 215) was collected using a self-administrated questionnaire from consumers with diverse socio-economic backgrounds through Survey Monkey. The well-known utilitarian and hedonic scales were adapted to suit the online shopping context, and utilised to collect empirical data for the study. Descriptive statistics, correlation analysis and structural equation modelling were applied to address the research objectives, and to test the hypothesised research model. Data and Empirical Analysis: The study found that four attributes/values, namely wider selection, efficiency, convenience and cost saving are determinants of consumers’ utilitarian motivation towards online shopping, while another set of four attributes/values, viz. adventure/explore, gratification, social and idea constituted consumers’ hedonic motivation towards online shopping were found. Furthermore, the study found that utilitarian and hedonic motivations are determinants of consumer attitude towards online shopping, while, in turn, consumer attitude was found to be a predictor of online purchasing intentions. Novelty: The study contributes to the literature on the contemporary online shopping phenomenon. Conducted in an emerging economy (South Africa), it provides a deeper understanding of, and an insight into how consumers behave and make decisions in an online environment. Policy Consideration: At a practical level, the paper has devised a tool (framework) for marketing practitioners to utilise in influencing consumer attitude towards online shopping and purchasing intentions, and ultimately conclude a sale through online transaction.